Selective, bifunctional Cu-WOx/Al2O3 catalyst for hydrodeoxygenation of fatty acids - Janampelli, Sagar; Sethia, Govind; Darbha, Srinivas (Catalysis Science & Technology, 2020)
Selective hydrodeoxygenation of oleic acid (OA; in a batch reactor, at 300 degrees C, 30 bar H-2 pressure, reaction time of 1 h and reactant-to-catalyst weight ratio of 2 g OA/0.2 g) forming n-octadecane in yields as high as 93% over a non-noble metal, sulfur-free, bimetallic Cu-WOx/Al2O3 catalyst is reported for the first time. Several Cu-WOx/Al2O3 compositions were prepared by a sequential wet-impregnation method and evaluated. A catalyst with 10 wt% Cu and 4 wt% W enabled the highest activity and selectivity. Upon adding WOx, the amount of moderate and strong acid sites increased and more Cu in the catalyst was in reduced electron-rich metallic (Cu-0) state. The crystallite size and dispersion of Cu were little affected. WOx promoted the fatty acid hydrodeoxygenation activity of Cu. While a monometallic Cu catalyst (10Cu/Al2O3) yielded n-octadecane and n-heptadecane along with high amounts of intermediate octadecanol and octadecanal products, the bimetallic catalyst (10Cu-4WO(x)/Al2O3) gave mainly n-octadecane. Acidity and the high amount of reduced Cu-0 species are responsible for the high catalytic hydrodeoxygenation performance of this bimetallic catalyst.